Synthesis, Biological Evaluation, and Molecular Modeling Studies of New Thiadiazole Derivatives as Potent P2X7 Receptor Inhibitors - Gonzaga, Daniel T. G.; Oliveira, Felipe H.; Ranke, N. L. von; Pinho, G. Q.; Salles, Juliana P.; Bello, Murilo L.; Rodrigues, Carlos R.; Castro, Helena C.; Souza, Hellen V. C. M. de; Reis, Caroline R. C.; Leme, Rennan P. P.; Mafra, João C. M.; et al. (Frontiers in Chemistry, 2019)
Twenty new 2-(1H-pyrazol-1-yl)-1,3,4-thiadiazole analogs were synthetized to develop P2X7 receptor (P2X7R) inhibitors. P2X7R inhibition in vitro was evaluated in mouse peritoneal macrophages, HEK-293 cells transfected with hP2X7R (dye uptake assay), and THP-1 cells (IL-1β release assay). The 1-(5-phenyl-1,3,4-thiadiazol-2-yl)-1H-pyrazol-5-amine derivatives 9b, 9c, and 9f, and 2-(3,5-dimethyl-1H-pyrazol-1-yl)-5-(4-fluorophenyl)-1,3,4-thiadiazole (11c) showed inhibitory effects with IC50 values ranging from 16 to 122 nM for reduced P2X7R-mediated dye uptake and 20 to 300 nM for IL-1β release. In addition, the in vitro ADMET profile of the four most potent derivatives was determined to be in acceptable ranges concerning metabolic stability and cytotoxicity. Molecular docking and molecular dynamics simulation studies of the molecular complexes human P2X7R/9f and murine P2X7R/9f indicated the putative intermolecular interactions. Compound 9f showed affinity mainly for the Arg268, Lys377, and Asn266 residues. These results suggest that 2-(1H-pyrazol-1-yl)-1,3,4-thiadiazole analogs may be promising novel P2X7R inhibitors with therapeutic potential.